Identification of Saltwater Intrusion Distribution in North Padang Cermin Area, Lampung, Indonesia - Alviyanda; Anjar Dwi Asterina; Redhatul Irma (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
The residential areas of North Padang Cermin are mainly located near the coastal area with a high level of groundwater use. Continuous groundwater use could potentially raise saltwater intrusion and lead to a decrease in groundwater quality. The research is conducted to identify the saltwater intrusion spread based on groundwater quality data. Geological observations were carried out to determine the geological conditions of the research area, followed by qualitative and quantitative hydrogeological observations by measuring TDS (Total Dissolved Solid), EC (Electrical Conductivity), pH, temperature, color, and taste. The Herzberg method was used to identify freshwater thickness against seawater intrusion. Hydrogeologically, the research area has four aquifer systems: aquifers with fissure and intergranular flow, aquifers with intergranular flow and wide-distribution productivity, aquifers with fissure and intergranular flow and local distribution, and aquifers with rare groundwater. Groundwater flow has a radial pattern with the most extensive hydraulic gradient with a value of 0.16 m towards the eastern part of the research area. The indications of seawater intrusion were found in the water samples measurement located on the east of the research area with water type of brackish–salty with a TDS value of 1,443 – 3,790 ppm and an EC of 3,000 – 7,580 (μS). Based on the Herzberg method, the distribution of seawater intrusion is estimated to occur at a depth of 36.8 m.